Remdesivir for Early COVID-19 Treatment of High-Risk Individuals Prior to or at Early Disease Onset—Lessons Learned - Lars Dölken; August Stich; Christoph D. Spinner (Viruses, 2021)
After more than one year of the COVID-19 pandemic, antiviral treatment options against SARS-CoV-2 are still severely limited. High hopes that had initially been placed on antiviral drugs like remdesivir have so far not been fulfilled. While individual case reports provide striking evidence for the clinical efficacy of remdesivir in the right clinical settings, major trials failed to demonstrate this. Here, we highlight and discuss the key findings of these studies and underlying reasons for their failure. We elaborate on how such shortcomings should be prevented in future clinical trials and pandemics. We suggest in conclusion that any novel antiviral agent that enters human trials should first be tested in a post-exposure setting to provide rapid and solid evidence for its clinical efficacy before initiating further time-consuming and costly clinical trials for more advanced disease. In the COVID-19 pandemic this might have established remdesivir early on as an efficient antiviral agent at a more suitable disease stage which would have saved many lives, in particular in large outbreaks within residential care homes.